1993
DOI: 10.1590/s0034-89101993000600008
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional factors in milk from Brazilian mothers delivering small for gestational age neonates

Abstract: CRUMACH, A.S. et al. Nutritional factors in milk from Brazilian mothers delivering small for gestacional age neonates. Rev. Saúde Pública, 27: 455-62, 1993. The composition of breast milk from brazilian mothers delivering low birthweight infants and its adequacy as a source of nutrients for this group has not yet been fully elucidated. A total of 209 milk samples from 66 women were analysed. The mothers were divided into three groups: G1, mothers delivering term babies of low birthweight (TSGA, n=16); G2, moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
8
0
5
Order By: Relevance
“…Outros estudos já comprovaram que o valor do crematócrito em amostras de LHP apresenta-se menor que o do LHC [30][31][32] . Wang relata que o congelamento e descongelamento do leite humano está associado à diminuição do crematócrito; entretanto, os efeitos desses processos na concentração de lipídeos, carboidratos e proteínas não se mostraram significativos 4 .…”
Section: Discussionunclassified
“…Outros estudos já comprovaram que o valor do crematócrito em amostras de LHP apresenta-se menor que o do LHC [30][31][32] . Wang relata que o congelamento e descongelamento do leite humano está associado à diminuição do crematócrito; entretanto, os efeitos desses processos na concentração de lipídeos, carboidratos e proteínas não se mostraram significativos 4 .…”
Section: Discussionunclassified
“…In the present study, the concentrations of sodium and potassium did not vary in the colostrum of hypertensive mothers, but they were higher in transitional and mature milk. Some studies have shown that sodium increases during the first 60 hours postpartum (Neville et al 1991;Grumash et al 1993), whereas others have reported no alterations in mineral levels of the milk of hypertensive mothers (Sírio et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have tested the creamatocrit value in samples of PHM and found it to be lower than in RHM. [30][31][32] Wang relates that freezing and defrosting human milk is associated with reductions in the creamatocrit, however the effects of these processes on the lipid, carbohydrate and protein concentrations were not found to be significant. 4 The calculations made to ascertain the energy content of the PHM samples tested in this study demonstrated that the caloric content of the samples was not the most suitable for guaranteeing the desired nutritional support to VLBW infants.…”
Section: Discussionmentioning
confidence: 99%